Flood Can Miami learn from Venice (or the opposite) - Washer, Christophe (AESOP, 2019)
On the one hand, “la Serenissima”, a millenary city, which saw its heyday between XIII and XV centuries. On the other “the Magic City”, famous for leisure and pleasure, born in the late nineteenth century from the encounter of two American pioneers. Apparently, they have nothing in common. Yet they share a lot in common. They are both situated in lagoon areas. They rely heavily on tourism and port activity for their economy. And, they find themselves at the frontline of climate change. Venice has always been confronted to flooding, but this condition has been worsening, due to over extraction from aquifers, which caused the city to subside, and to sea level rise. In contrast, flooding isn’t part of Miamians’ culture and tradition. In recent years, however, with climate change bringing about higher rainfalls and storm surges, and causing sea level to rise, Miami has been experiencing more and more floods. Both cities are now highly jeopardised. After developing on the differences and similarities between Venice and Miami, this article proposes to investigate what answers these cities come with to address climate change effects, and to question what they could learn from each other.
Keywords: la Serenissima; millenary city; the Magic City; lagoon areas; climate change; higher rainfalls; sea level rise; floods